Vitamin D receptor (VDR) gene polymorphism and osteoporosis risk in White British men. (4th July 2019) - Kow, Melissa; Akam, Elizabeth; Singh, Puneetpal; Singh, Monica; Cox, Nick; Bhatti, Jasvinder Singh; Tuck, Stephen P.; Francis, Roger M.; Datta, Harish; Mastana, Sarabjit
Abstract: In this study, VDR gene ApaI (rs7975232), BsmI (rs 1544410) and TaqI (rs731236) genotypes were compared in men with osteoporosis and male controls. Osteoporosis affects around 20% of all men and overall mortality in the first year after hip fracture is significantly higher in men than women, yet the genetic basis of osteoporosis is less well studied in males. This study consisted of White British males; 69 osteoporosis patients and 122 controls. BMDs at the lumbar spine (vertebrae L1–L4) and hip (femur neck) were measured by dual-energy X-ray absorptiometry (DEXA). The VDR gene ApaI, BsmI and TaqI genotypes were determined by polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) and association analysis was carried out at genotype and haplotype level. Our study suggests that TaqI polymorphism CC genotype frequency is lower in controls and further analysis of genotypes and BMD revealed a significant effect of TaqI polymorphism on Lumbar spine BMD. Two haplotypes (GCC and AAT) were associated with increased osteoporosis risk. In conclusion, VDR gene TaqI polymorphism in recessive mode had a significant effect on lumbar spine BMD within our study. Haplotypes GCC and AAT increase the risk of osteoporosis among White British males.